2020
DOI: 10.3390/jfmk5020026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Enriched Sports Activities-Program on Executive Functions in Italian Children

Abstract: Physical activity (PA) during childhood plays an important role in brain development. This role is played in both the structural domain, prefrontal cortex area, and in the functional domain, involving the higher cognitive functions, including the executive functions (EF). Working memory (WM), inhibition, and switching as fundamental EF were investigated in an Italian children sample before and after four months of an Enriched Sports Activities-Program (ESA-Program). EFs were assessed at pre-test and post-test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
0
4
0
1
Order By: Relevance
“…Indeed, our intervention focused on cognitive challenge generated by multisport games. While cross-sectional evidence shows that the practice of team sports is consistently associated with better inhibitory performance [ 39 , 40 , 41 ], interventional research mostly failed to find benefits of cognitively enriched sport game interventions for pure measures of inhibition [ 97 , 98 , 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our intervention focused on cognitive challenge generated by multisport games. While cross-sectional evidence shows that the practice of team sports is consistently associated with better inhibitory performance [ 39 , 40 , 41 ], interventional research mostly failed to find benefits of cognitively enriched sport game interventions for pure measures of inhibition [ 97 , 98 , 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nuestros resultados respaldan los obtenidos en un trabajo desarrollado en sujetos infantiles con obesidad, en el que se consiguieron diferencias significativas en la asociación entre Página 77 la AF y la MT cuando la primera era intensa (Mora- González, et al 2019). También se accede a la misma relación en la investigación realizada por Alesi, et al (2020), al producirse mejoras significativas en la MT del GE cuando se le implementa un programa aumentado de Educación Física.…”
Section: Discussionunclassified
“…Cognitive flexibility : We measured the children’s cognitive flexibility with the 25 circles version of the Trail-Making Test (TMT; Lezak et al, 2004). Though Retian (1979) described this as an adult version of the TMT, it has been used in many child studies (Alesi et al, 2020; Elghoul et al, 2014; Howie et al, 2015; Ledochowski et al, 2019) and it has been shown to be a valid and appropriate test of cognitive flexibility for children (Howie et al, 2015; Lezak et al, 2004) with moderate test-retest reliability in children (Howie et al, 2015) and an intraclass correlation coefficient of .50–.60. The TMT is comprised of two parts, A and B, each consisting of 25 circles distributed on a sheet of paper (Reitan, 1979).…”
Section: Methodsmentioning
confidence: 99%